2021
DOI: 10.3803/enm.2021.979
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Control of the Feeding Circuit

Abstract: There is increasing evidence demonstrating that reward-related motivational food intake is closely connected with the brain's homeostatic system of energy balance and that this interaction might be important in the integrative control of feeding behavior. Dopamine regulates motivational behavior, including feeding behaviors, and the dopamine reward system is recognized as the most prominent system that controls appetite and motivational and emotional drives for food. It appears that the dopamine system exerts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 75 publications
0
13
0
2
Order By: Relevance
“…After the establishment of this baseline feeding curve, we gave the mice access to more palatable high fat diet (HFD) (Figures 1E,F). We chose to provide the mice with about one-half of the amount of daily caloric intake worth of HFD to avoid Frontiers in Physiology frontiersin.org over-eating of the mice with harmful metabolic consequences (Coccurello and Maccarrone 2018;Baik 2021). Due to the construction of the feeding cubes (Figure 1A), the mice had to eat first the HFD before having access to normal diet (ND) ad libitum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the establishment of this baseline feeding curve, we gave the mice access to more palatable high fat diet (HFD) (Figures 1E,F). We chose to provide the mice with about one-half of the amount of daily caloric intake worth of HFD to avoid Frontiers in Physiology frontiersin.org over-eating of the mice with harmful metabolic consequences (Coccurello and Maccarrone 2018;Baik 2021). Due to the construction of the feeding cubes (Figure 1A), the mice had to eat first the HFD before having access to normal diet (ND) ad libitum.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was another demonstration of the power of more palatable food to override the inhibitory signals from the homeostat system, especially, when this kind of food was given during the rest phase of an animal. It has been suggested that continuous food uptake at the wrong phase, i.e., the rest phase, increased the risk of developing metabolic syndrome and obesity ( Coccurello and Maccarrone 2018 ; Baik 2021 ). An interesting therapeutic approach has been developed based on these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that 5-HT and DA have a role in controlling food intake. [40] In anorexic animals, the hypothalamic ventromedial nucleus exhibits elevated 5-HT levels and reduced DA levels, along with increased levels of the dopaminergic receptors D1 and D2. [41] Therefore, the decreased weight of pups observed at PND 7, 14, and 21 may be due to changes in serotonergic and/or dopaminergic neurotransmission by VLZ and VOX exposure during prenatal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…While dopamine signaling is mostly recognized as a regulator of hedonic feeding, dopaminergic neurons are also located across the hypothalamus, suggesting that they may be directly involved in homeostatic feeding regulation ( Baik, 2021 ). Known as the A12 group, dopaminergic neurons located in the Arc were reported to promote feeding by inhibiting Arc POMC neurons via GABAergic synapses, and PVN via both DA and GABAergic synapses ( Zhang and van den Pol, 2016 ).…”
Section: Food As a Zeitgebermentioning
confidence: 99%